2018
DOI: 10.1021/acsami.7b19414
|View full text |Cite
|
Sign up to set email alerts
|

Selective Adsorption of Ethane over Ethylene in PCN-245: Impacts of Interpenetrated Adsorbent

Abstract: The separation of ethane from ethylene using cryogenic distillation is an energy-intensive process in the industry. With lower energetic consumption, the adsorption technology provides the opportunities for developing the industry with economic sustainability. We report an iron-based metal-organic framework PCN-245 with interpenetrated structures as an ethane-selective adsorbent for ethylene/ethane separation. The material maintains stability up to 625 K, even after exposure to 80% humid atmosphere for 20 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 36 publications
(73 reference statements)
3
78
0
Order By: Relevance
“…Among different temperatures, the adsorption uptakes of ethane always exceed those of ethylene, reflecting ethane‐selective adsorption behavior of Zr‐bptc. At ambient pressure, ethane and ethylene uptakes in Zr‐bptc are 3.72 and 3.50 mmol/g at 288 K, 3.26 and 3.08 mmol/g at 298 K, 2.74 and 2.54 mmol/g at 308 K. The ethane uptake of Zr‐bptc (3.26 mmol/g) at 298 K and 100 kPa is superior to many reported ethane‐selective adsorbents (Table S3), such as activated carbon (2.52 mmol/g), ZIF‐8 (2.50 mmol/g), ZIF‐69 (2.20 mmol/g), ZIF‐4 (2.30 mmol/g), MAF‐49 (1.56 mmol/g), UiO‐66 (2.28 mmol/g) (Figure S11), Cu(ina) 2 (1.99 mmol/g), Cu(Qc) 2 (1.85 mmol/g), and Fe 2 (O 2 )(dobdc) (3.03 mmol/g), but the ethane uptake of Zr‐bptc is inferior to PCN‐245 (3.27 mmol/g) (Figure S12), IRMOF‐8 (4.00 mmol/g), and Ni(bdc)(ted) 0.5 (5.0 mmol/g) (Figure S13). …”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Among different temperatures, the adsorption uptakes of ethane always exceed those of ethylene, reflecting ethane‐selective adsorption behavior of Zr‐bptc. At ambient pressure, ethane and ethylene uptakes in Zr‐bptc are 3.72 and 3.50 mmol/g at 288 K, 3.26 and 3.08 mmol/g at 298 K, 2.74 and 2.54 mmol/g at 308 K. The ethane uptake of Zr‐bptc (3.26 mmol/g) at 298 K and 100 kPa is superior to many reported ethane‐selective adsorbents (Table S3), such as activated carbon (2.52 mmol/g), ZIF‐8 (2.50 mmol/g), ZIF‐69 (2.20 mmol/g), ZIF‐4 (2.30 mmol/g), MAF‐49 (1.56 mmol/g), UiO‐66 (2.28 mmol/g) (Figure S11), Cu(ina) 2 (1.99 mmol/g), Cu(Qc) 2 (1.85 mmol/g), and Fe 2 (O 2 )(dobdc) (3.03 mmol/g), but the ethane uptake of Zr‐bptc is inferior to PCN‐245 (3.27 mmol/g) (Figure S12), IRMOF‐8 (4.00 mmol/g), and Ni(bdc)(ted) 0.5 (5.0 mmol/g) (Figure S13). …”
Section: Resultsmentioning
confidence: 88%
“…The mass loss of 32.1% for H 4 bptc is close to the theoretical value (32.4%) calculated from the formula Zr 6 O 4 (OH) 4 (bptc) 3 . Therefore, Zr‐bptc is thermally stable to 702 K. The thermal decomposition temperature of Zr‐bptc (702 K) outperformed most reported ethane‐selective MOFs, such as IRMOF‐8 (673 K), PCN‐250 (673 K), PCN‐245 (625 K), Ni(bdc)(ted) 0.5 (673 K), ZIF‐69 (643 K), and MIL‐142A (573 K), but slight lower than UiO‐66 (739 K) . The high thermal stability of Zr‐bptc and UiO‐66 probably lies on the strong Zr‐O coordination bonds and the 12‐connected Zr 6 (μ 3 ‐O) 4 (μ 3 ‐OH) 4 (COO) 12 SBU of Zr‐bptc and UiO‐66.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, Chen et al reported another iron MOF MIL‐142A with ethane adsorption selectivity (5.8–1.5 in the pressure range of 0–100 kPa) based on the ligand combination of terephthalate and 1,3,5‐tris(4‐carboxyphenyl)benzene . Recently, Lv et al reported an interpenetrated iron MOF PCN‐245 for ethane/ethylene separation . Metropolis MC calculations suggested that the interpenetrated structure of PCN‐245 creates greater interaction affinity for ethane than ethylene through the crossing organic linkers, which could account for the higher uptake of ethane and ethane/ethylene separation in the adsorption column containing PCN‐245.…”
Section: Metal–organic Framework For Adsorptive Light Olefin/paraffimentioning
confidence: 99%
“…[131] Recently, Lv et al reported an interpenetrated iron MOF PCN-245 for ethane/ethylene separation. [132] Metropolis MC calculations suggested that the interpenetrated structure of PCN-245 creates greater interaction affinity for ethane than ethylene through the crossing organic linkers, which could account for the higher uptake of ethane and ethane/ethylene separation in the adsorption column containing PCN-245.…”
Section: Separation Based On the Difference Of Van Der Waals Interactmentioning
confidence: 99%